SURVEY SANITASI PERUMAHAN DI DESA JUHAR TARIGAN KECAMATAN JUHAR TAHUN 2016 - Susanti Perangin-Angin (Jurnal Mutiara Kesehatan Masyarakat, 2017)
Homes for human beings have the meaning of a place to unwind, rest after tiring to perform daily obligations, as a place to mingle with the family, as a place to protect themselves from danger, as a symbol of social status, a place of wealth. In relation to that, the law of the Republic of Indonesia Number 36 Year 2009 on the Health program states that the highest degree of public health is achieved through the implementation of health development entitled to residence and to have a good and healthy environment. This research is a descriptive research to describe the Condition of Housing Sanitation in Juhar Tarigan village of Juhar Subdistrict Karo District in 2016 where the method of sampling is simple random sampling. For the determination of sample representation of population determined by the sample of 70 KK. The result of this research shows that the most dominant home construction is no house fence as much as 96%, no gate fence as much as 96%, home page is gross as much as 64,3%, less regular plant as much as 35,7%, construction of house building not fulfilled the requirement of 47.1%, the window area fulfills the requirement of 42.9%, the cleanliness of many spider webs as much as 34.3%, the ventilation in the house is about 30%, the number of flies is 3-5 flying by 50% , the number of cockroaches 3 was 67.2%, the number of mosquitoes less than 5 was 67.2%, the number of mice occasional rats was 51.4%, 68.6% was plastered, 57.6% , 1% and kitchen smoke holes as much as 65.7%. The most dominant environment and facilities are the RT wastewater drainage channeled into open riol as much as 61.4%, the garbage collection system is collected and burned by 51.4% the drinking water supply system exists drinking water from outside as much as 51.5%, toilet types are goose neck latrine as much as 64.3% and there is also no toilet as much as 30%. The result of the research concluded that the state of sanitation of housing still lack of health requirement. In this study it is suggested that the community should pay attention to the construction of their houses and their environmentally friendly facilities and facilities so that their home is healthy and will not cause illness if they are aware of the importance of a healthy home Keywords: sanitation, home, construction, facilities and prasana, environment